2018
DOI: 10.1016/j.gie.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinical outcome of colonic stents in patients with malignant large-bowel obstruction because of extracolonic malignancy

Abstract: This study represents the largest retrospective series of colonic stent placement for LBO in ECM patients in the literature. Our technical success rate of 75.9%, clinical success rate of 54.5%, and 3-month stent occlusion rate of 14.7% suggest that stent placement is a viable palliative option for patients with advanced disease because of ECM. Patients with peritoneal carcinomatosis and multifocal disease have reduced technical and clinical success. However, these factors should not dissuade an attempt at sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 25 publications
(31 reference statements)
1
47
0
Order By: Relevance
“…The four selected studies have similar characteristics ( Table 1 ) 10 13 23 24 . CSEMS dwelling time ranged from 3 to 6 months and the interval to replace the plastic stents ranged from 6 to 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four selected studies have similar characteristics ( Table 1 ) 10 13 23 24 . CSEMS dwelling time ranged from 3 to 6 months and the interval to replace the plastic stents ranged from 6 to 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…CSEMS dwelling time ranged from 3 to 6 months and the interval to replace the plastic stents ranged from 6 to 16 weeks. The study by Kaffes et al 6 was the only one that used metallic prostheses with greater diameter at the ends and did not mention minimum follow-up time; the other three studies 10 23 24 reported follow-up of at least 1 year. Data were extracted from published material and there was no need to access original data from the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Performance metrics during colonoscopy training can be used to indicate readiness for independent practice. The study by Bitar et al 1 is therefore a welcome addition to the colonoscopy training literature. The distinguishing feature of fellow seniority (and presumably competence) was the "efficiency" or speed with which the colon was intubated and adenomas detected and removed.…”
Section: Impact Of Fellowship Training Level On Colonoscopy Quality Amentioning
confidence: 94%
“…Enteral stenting is more suitable for patients with advanced malignancy who are too sick to undergo surgery, and it could potentially offer a shorter hospital stay with lower medical costs. However, it is less effective in patients with PC in both upper and lower gastrointestinal obstruction with a significant risk of stent failure from tumor ingrowth, inadequate expansion, clogging, or migration [8][9][10][11]. Having predictors of treatment success to identify ideal candidates for enteral stenting is, therefore, critical.…”
Section: Patients and Methods Consecutive Inpatients With Mgiomentioning
confidence: 99%